Jogos e brincadeiras na Educação Infantil: o papel do professor no processo ensino-aprendizagem das crianças - Santos, Tolly Ohanna Queiroz dos (Brasil, 2025)
In the age of screens, playing is once again required as a space/time/moment of interaction, learning and development of motor, cognitive and emotional skills. This article is the result of qualitative research whose objective was to investigate the role of the teacher in mediating games and games in the teaching and learning process in early childhood education. Therefore, this study had the following authors as its theoretical framework: Kishimoto (2011), Angotti (2010), Luckesi (1998), Maluf (2009), Almeida (1998), Figueiredo e Souza (2021), Vigotski (2018, 2021) , Martins, Afrantes and Facci (2020), Montessori (2002). The field research was carried out in a public Children's Educational Center located in the city of Parintins - AM, and involved two teachers who work in the morning shift, in the respective 1st and 2nd period classes, with children aged 4 to 5 years and 11 months. The data collection instrument was based on participant observation and semi-structured interviews, which allowed an understanding of the use of playful strategies in the daily activities of the Educational Center. It was found that teachers recognized games and games as essential elements for child development, however, there was a lack of educational intentionality when proposing toys and games, as well as the environment/spaces (internal and external) unfavorable for pedagogical practice in early childhood education.